Evaluation of feed digestibility in goats based on palm oil industry waste and fisheries in Southwest Papua - Wijaya, Andi; Aditama, Rizal; Firman, Sri; Puspitasari, Reza; Duwith, Alfian; Iba, Antonius (Jurnal Ilmu Peternakan Terapan, 2025)
Palm oil and fishery waste are recognized as potential environmental concerns, necessitating their processing for reuse as feed material. This study aimed to evaluate the digestibility of feed materials based on palm oil waste and fish waste, utilizing EM4 and Aspergillus niger in goats. Six male goats was randomly used to assess the digestibility of dry matter (DM) and crude protein (CP) in six types of feed, each featuring distinct waste and fermenter, employing a 6x6 Latin Square Design. Digestibility data were obtained through in vitro and in vivo methods. The in vivo method showedthat T2, made from palm oil waste and Aspergillus niger, demonstrated the highest DM digestibility of 62.10±7.64%. Conversely, the highest CP digestibility was found in T4, which consists of fish waste with Aspergillus niger, yielding an average protein digestibility value of 67.21±9.81%. In contrast, the in vitro method indicated that the highest DM digestibility occurred in T6, which combines palm and fish waste with Aspergillus niger, averaging 65.25±5.59%. Meanwhile, T4 (fish waste with Aspergillus niger) showed a protein digestibility of 71.69±8.7%. These findings suggest that palm oil waste and fish waste can be tailored to meet livestock nutritional requirements. Furthermore, they indicate that utilizing Aspergillus niger is a more cost-effective approach compared to EM4.